Manfaat gerakan salat untuk meningkatkan fleksibilitas punggung bawah pada pengrajin kain blongsong di Kota Palembang - Indri Seta Septadina; Rulan Adnindya; Wardiansyah Wardiansyah; Tri Suciati (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2020)
Prayer is a worship performed by Muslims at least five times a day and night. Prayer is a set of physical movements while reciting verses of the Koran that are adapted to each position and movement in prayer. Prayer movements stretch a number of muscles and nerves, which provide constant physical therapy to all joints in the body so as to prevent arthritis and back pain. In this activity an assessment of lower back flexibility was carried out on the craftsman of the cloth in the village of Tuan Kentang in the District of Seberang Ulu 1 in the city of Palembang and education on the benefits of the prayer movement as an effort to care for lower back flexibility. Lower back flexibility in the group of men is very good (36.4%), good (36.4%), and sufficient (27.2%). While in the group of women, the value of flexibility is also very good (47.4%), good (15.8%), and sufficient (36.8%). None of the participants had impaired lower back flexibility.